Mediation Impact of Physical Literacy and Activity Between Psychological Distress and Life Satisfaction Among College Students During COVID-19 Pandemic. (March 2023) - Dong, Xiaoxi; Huang, Fan; Shi, Xiangyun; Xu, Menglin; Yan, Zengyin; Türegün, Mehmet
The study aims to examine the mediation effects of physical literacy and physical activity behavior in a relationship between psychological distress and life satisfaction among Chinese college students during the real-life Coronavirus disease pandemic (COVID-19) circumstance. This study implemented a cross-sectional design, and 1, 516 participants from 12 universities participated in this study. Structural equation modeling was used to examine a hypothesized model. The findings indicated an acceptable model fit ( X 2 [61] = 508.2, Comparative Fit Index [CFI] = 0.958, Tucker Lewis Index [TLI] = 0.946, Root Mean Square Error of Approximation [RMSEA] = 0.076, 90% CI [0.070, 0.082], Standardized Root Mean Square Residual [SRMR] = 0.047). The results indicated that college students with low participation in physical activity could experience less than healthy living conditions. The findings offered empirical support to the theory that physical literacy could advance individuals' healthy living by promoting physical activity participation. The study suggested that educational institutions and physical activity programs should cultivate individuals' physical literacy in order to promote lifelong healthy living.